Advancing Elementary Vocabulary Education with Wordwall-Based Digital Media - I Komang Yogi Pratama Wedananta; I. G. A. Lokita Purnamika Utami; G. A. P. Suprianti (Journey: Journal of English Language and Pedagogy, 2024)
In Indonesia, the education curriculum underwent numerous changes, with the most recent being the Merdeka curriculum. Vocabulary was a crucial component in English language learning. This study aimed to develop Wordwall-based learning media for vocabulary using the "My Next Words" book at SD Negeri 1 Baktiseraga for fourth-grade students in the second semester. The research involved classroom observations, interviews with English teachers, and analysis of the curriculum and students' needs. In the planning stage, the design of Wordwall games focused on vocabulary learning objectives aligned with the "My Next Words" curriculum. Development included creating Wordwall games, selecting templates, types of games, and integrating interactive features. After development, Wordwall products were evaluated and approved by education and technology experts, then integrated into the learning process for fourth-grade students at SD Negeri 1 Baktiseraga. Evaluation assessed the effectiveness of Wordwall in enhancing students' vocabulary comprehension, with experts reviewing the quality of learning materials, user experience, and its impact on students' learning motivation. The results indicated that Wordwall was effective in improving English vocabulary acquisition and making learning more engaging and motivating for students.